Staged, Open, No-Ischemia Nephron-Sparing Surgery for Bilateral-Multiple Kidney Tumors in a Patient with Birt-Hogg-Dubé Syndrome. (24th April 2012) - Tefekli, Ahmet; Akkaya, Ayşe Deniz; Peker, Kamil; Gümüş, Terman; Vural, Metin; Cezayirli, Fatin; Musaoglu, Ahmet; Esen, Tarık
Abstract : Hereditary kidney cancer patients with bilateral multiple kidney tumors represent challenges in the era of rapidly growing minimal invasive treatment techniques. Birt-Hogg-Dubé Syndrome (BHDS) is an autosomal dominant genodermatosis characterized by a triad of benign skin tumors (fibrofolliculomas, trichodiscomas, acrochordons) together with an increased risk of developing malignant renal tumors and pulmonary disease such as pneumothoraces and multiple lung cysts. The morbidity and mortality of the affected patients is determined by the presence of the kidney tumors, which tend to be multifocal and bilateral, as observed in other hereditary kidney cancer syndromes like von Hippel-Lindau disease, familial leiomyomatosis, and hereditary papillary renal cell carcinoma. Herein, a patient with BHDS, presenting with synchronous bilateral multiple kidney tumors, is reported. The report describes the management of kidney tumors with two-stage open nephron-sparing surgery in which the nonvascular clamping technique was utilized.